2021
DOI: 10.3390/ijms22031257
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid-Targeted Stimuli-Sensitive Nanomicelles Co-Encapsulating Paclitaxel and Ritonavir to Overcome Multi-Drug Resistance in Metastatic Breast Cancer and Triple-Negative Breast Cancer Cells

Abstract: Active targeting and overcoming multi-drug resistance (MDR) can be some of the important attributes of targeted therapy for metastatic breast cancer (MBC) and triple-negative breast cancer (TNBC) treatment. In this study, we constructed a hyaluronic acid (HA)-decorated mixed nanomicelles-encapsulating chemotherapeutic agent paclitaxel (PTX) and P-glycoprotein inhibitor ritonavir (RTV). HA was conjugated to poly (lactide) co-(glycolide) (PLGA) polymer by disulfide bonds (HA-ss-PLGA). HA is a natural ligand for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 48 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…This formulation also increased the production of IFN-γ and lung parenchyma protection to a level similar to that in mice vaccinated intramuscularly four times the dosage of naked pDNA encoding HSP65 [115]. In addition, intranasal immunization with liposome-based DNA vaccine provided complete protection against influenza after a viral challenge assay [116]. Mice immunized intranasally with liposome-encapsulated pDNA encoding hemagglutinin (HA) protein, but not naked plasmid, were found to produce strong serum IgA/IgG responses and increased IgA titers in bronchoalveolar lavage fluid (BALF) [117].…”
Section: Liposomes and Niosomesmentioning
confidence: 73%
“…This formulation also increased the production of IFN-γ and lung parenchyma protection to a level similar to that in mice vaccinated intramuscularly four times the dosage of naked pDNA encoding HSP65 [115]. In addition, intranasal immunization with liposome-based DNA vaccine provided complete protection against influenza after a viral challenge assay [116]. Mice immunized intranasally with liposome-encapsulated pDNA encoding hemagglutinin (HA) protein, but not naked plasmid, were found to produce strong serum IgA/IgG responses and increased IgA titers in bronchoalveolar lavage fluid (BALF) [117].…”
Section: Liposomes and Niosomesmentioning
confidence: 73%
“…At present, many small molecule compounds targeting STAT3 signal have entered the clinical trials, including WP1066 (targeting JAK2) [24] , AZD9150 (the antisense oligonucleotide of STAT3) [25] , C188-9 (targeting the STAT3 SH2 domain) [26] , OPB-31121 (targeting JAK2) [27] , OPB-51602 (targeting the STAT3 SH2 domain) [28] , Ruxolitinib (a JAK1/2 inhibitor) [29] , Ritonavir (a P-glycoprotein inhibitor) [30] , TT-00420 (an aurora kinase A/B inhibitor), Icaritin (a regulator of MAPK/ERK/JNK and JAK2/STAT3/AKT signals) [31] and Napabucas (targeting the STAT3 SH2 domain) [32] , et al However, they are limited due to the indirect targeting, weak selectivity, low bioavailability, lack of therapeutic advantage or high toxicity. Compared with these compounds, SMY002 has the advantage of direct targeting STAT3 and can remarkably reduce the growth and dissemination of transplanted TNBC cells in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Gel might be one of most convenient agents for application in a limited and irregular space, such as the intrauterine space, and most gel agents commonly contain derivatives of hyaluronic acid (HA) with other main components, such as sodium D-glucuronate and N-acetyl-glucosamine, which is a linear polysaccharide with 25,000 repeating disaccharide units, composed of major supportive and protective components in a vitreous body, saliva, synovial fluid, cartilage, skin, and umbilical cord [157][158][159][160][161][162][163]. Earlier reports have shown that the application of CHA gel has reduced the severity of postoperative IUA after hysteroscopic procedures [86,109,111,112].…”
Section: Gels As Anti-adhesive Agentsmentioning
confidence: 99%